ASSESSMENT METHODS OF USE OF INNOVATIONS IN BUSINESS SUBJECTS - Ahmedov Oybek Turgunpulatovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article presents ideas about methods of evaluation of the use of innovations in small business entities and scientific proposals and practical recommendations aimed at their improvement and effective use of innovations in the development of small business entities.